AI and Art Design: A Case Study of Space Opera House - Sun, Ruochen (Transactions on Social Science, Education and Humanities Research, 2024)
With the rapid advancement of artificial intelligence (AI) technology, AI painting, as an emerging technique, is gradually showcasing its unique charm and broad application prospects in the field of art design. This paper takes the representative AI painting Space Opera House as an example to conduct an in-depth analysis of AI painting from the perspectives of visual language and aesthetic expression. It explores the challenges and opportunities AI presents to traditional art design and further examines the current application and future development directions of AI in art design. The research results indicate that AI painting offers significant advantages in enhancing artistic creation efficiency, enriching artistic expression methods, and achieving personalized design. However, it also faces challenges in terms of originality and aesthetic diversity.